In Vitro Propagation and Mutation Induction of Dendranthema Grandiflora Tzvelev - Mon, Mi Chan (2006)
The genus Dendranthema (Family: Asteraceae) is a popular cut flower or pot plant species of high economic value cultivated around the world. The genus has more than 100 species of annuals and perennial herbs and shrubs used as floral crops as well as tea and source of other products such as pyrethrum. In vitro propagation using meristems, shoot tips etc. have been successfully applied as a means of large-scale production system for disease-free plants. The present study is carried out in two parts: in vitro propagation and mutation induction with the objectives of developing a protocol for an in vitro method of propagation using ray florets and creation of variations in Dendranthema grandiflora Tzvelev by combining the techniques of in vitro culture and radiationinduced mutagenesis.In developing protocol for rapid propagation, in vitro culture was established by using ray florets on two types of basal media, such as Murashige and Skoog (MS) and Gamborg (B5) media, containing various levels of 6-benzylaminopurine (BAP) (0, 0.5, 1.0 and 2.0 mg/L) and α–naphthaleneacetic acid (NAA) (0, 0.2, 0.5, 1.0 and 2.0 mg/L). In this study the highest percentage of callus formation was observed after 8 weeks on MS medium supplemented with 2.0 mg/L BAP and 1.0 mg/L NAA. However, the highest number of shoot multiplication was obtained from MS basal medium containing 2.0 mg/L BAP and 1.0 mg/L NAA. No growth responses were observed on MS and B5 basal media with BAP alone, whereas some roots developed on NAA alone in both types of basal media. After 10 weeks of culture many explants turned brown and died in the B5 basal medium. The highest callus proliferation in terms of fresh and dry weight as established on MS basal media containing 2.0 mg/L BAP and 1.0 mg/L NAA followed by treatment with 2.0 mg/L BAP with 1.0 and 2.0 mg/L NAA after 20 weeks of culture. The highest number of adventitious shoot formation (6.0 shoots per explant) was observed in MS medium supplemented with 2.0 mg/L BAP and 1.0 mg/L NAA. There were significant interactions between both growth regulators on the number of shoot per explant and height of shoots produced. In the radiation-induced mutagenesis study, irradiation treatments was performed on callus derived from ray florets, and on fresh ray florets using gamma rays from 60Co source at levels of 0 Gy, 10 Gy, 20 Gy, 30 Gy, 40 Gy and 50 Gy at a dose rate of 1.858 Gy/sec. Radiosensitivity test recorded a 100 % survival rate of callus on control treatment and subsequent decrease on treatments at higher doses. The highest growth of callus was observed in control treatment and subsequently growth rate decreased correspond to increasing doses. Similarly, irradiated ray florets recorded a 100% survival rate in the control treatment. Treatments at 10, 20, 30, 40 and 50 Gy gave survival rates of 83.3%, 73.3%, 26.6%, 23.3% and 6.6% respectively. The study concluded that the optimum dose for ray floret on growth rate of callus and survival were between 18.8 - 28.4 Gy. The optimum dose for irradiated callus based on growth rate and survival were between 26.9 - 36.2 Gy. The results from the experiments indicated that mutation induction can be performed on both ray florets and callus at LD50 18.8 - 28.4 Gy and 26.9 - 36.2 Gy respectively. The formation of shoots was observed on control (0 Gy) and 10 Gy treatments. The mean number of adventitious shoots from non-irradiated samples (control) was 2.72 ± 0.09 compared to 2.5 ± 0.18 for treatment at 10 Gy. No growth responses were observed from ray florets culture at all levels of treatment. Therefore, the development of new variety through mutation induction of Dendranthema, it is recommended to irradiate the explants at 10 Gy or lower.Amplified Fragment Length Polymorphism (AFLP) technique was carried out to detect the variation on genomic DNA of callus samples irradiated at different doses. The highest numbers of polymorphic bands were observed with primer combinations E-AGC + M-CAG at 20 Gy and E-AGG + M-CAT at 10 Gy. The smallest number of polymorphic bands was found with primer combination EAAG + M-CTC at 30 and 40 Gy. Primer combination E-ACG + M-CAA produced the most number of polymorphic bands (80) when compared to other primer combinations which were used in the experiment. There were no definite correlation between the different levels of irradiation to the number of polymorphic bands and unique polymorphic bands detected. Higher numbers of polymorphic bands and unique polymorphic bands were detected by the various primer combinations at doses 10 and 20 Gy.